Plant genotyping : the DNA fingerprinting of plants (CABI, 2001)
Plant genotype analysis can be used for the identification of plants in commerce, plant breeding and research. This book examines the technology available and their application in the analysis of wild plant populations, germplasm collections and plant breeding. Special attention has been paid to microsatellite analysis, single nucleotide polymorphism (SNP) markers and new technologies, such as microarrays and non-gel based analysis of markers. Some 21 chapters are presented in 5 sections: molecular markers available for use in plant genotyping (4 chapters); genotyping plant genetic resource collections (2 chapters); genotyping cultivated and wild germplasm (5 chapters); development of molecular markers for use in plant genotyping (4 chapters); and technical developments and issues in plant genotyping (6 chapters). Studies on cultivated and wild germplasm of Melaleuca alternifolia, Colocasia esculenta, sugarcane, wheat and barley are reported. A subject index is supplied.